Perhubungan antara sistem komunikasi pampasan dan kepuasan kerja: adakah keadilan prosedur memainkan peranan bersyarat? - Ismail, Azman; Ismail, Abdul Fatah; Mohd Shariff, Mohd Noor (Universiti Utara Malaysia, 2007)
Compensation management literature has highlighted that the strength of relationship between a compensation communication system and individual attitudes and behaviours would change when feelings of procedural justice are present in organisations. This empirical evidence is used as a guideline to develop and test a conceptual framework for this study using data gathered from in-depth interview and survey questionnaire methods. The sample of this study was 99 respondents who had completed the survey questionnaire forms. Outcomes of hypotheses testing using a hierarchical multiple regression analysis showed that knowledge about pay systems has invoked employees’ feelings of procedural justice, and this might lead to increased job satisfaction. Conversely, immediate boss treatment had not invoked individuals’ feelings of procedural justice, and this could lead to decreased job satisfaction. These outcomes could be influenced by the external factors, such as compensation management cultures that have been practised in the studied organisation. This study affirms that procedural justice does act as a partial moderator in the pay system model of on ICT company in Kuching, Sarawak. Thus, the implications of this study on compensation theory and practice, methodological and conceptual limitations, as well as suggestions for future research are also discussed.